Germline inherited small RNAs facilitate the clearance of untranslated maternal mRNAs in C. elegans embryos - Piergiuseppe Quarato (Nature Portfolio, 2021)
In animal embryos, maternally deposited mRNAs are degraded by several different mechanisms. Here the authors show that C. elegans embryos inherit antisense pool of small RNAs which are loaded into CSR-1 and cleave complementary maternal mRNAs.